High Resolution Change Detection of Erosion Patterns in Badlands with the Use of UAS Datasets - Konsolaki, A.; Vassilakis, E; Kotsi, E.; Lekkas, E. (IAG Reg. Conf. of Geomorphology, 2023)
Badlands are among the most intricate and complex types of erosion landscapes typically formed from soft sedimentary rock, such as shale, clay, and sandstone, which can be intensively eroded by precipitation processes. The erosion produces steep slopes, deep canyons, and peculiar geomorphological features that are highly related to this type of landforms. The SE part of Zakynthos Island, located at the Ionian Sea (western Greece), is characterized by such kind of landscape dominated by high inclined marly sandstone formations, of Pliocene age. Besides their high contribution to the geo-diversity of the Island, the Gerakas Badlands are characterized by ecological significance since they host a nesting site for the endangered loggerhead sea turtle, within the National Marine Park of Zakynthos. The study of badlands can offer insights into the processes and mechanisms of erosion since due to their unique rock properties, including their high clay content, low organic matter, and low infiltration capacity, they are exceptionally vulnerable to erosion. Therefore, their relatively rapid reshaping and the processes that affect these geomorphological features could be measured with innovative techniques and equipment. We describe a methodology based on the advancement of technological means and particularly the use of Unmanned Aerial Systems (UAS) which provides detailed information on micro-topography, erosion patterns, and other key features by applying change detection over time. The period needed for monitoring badlands to identify erosion patterns can vary depending on various factors such as the scale of the study area, the climate conditions, and the specific objectives of the study. In this case, the data acquisition was accomplished in two phases three years apart, which were used to create a series of DSMs along with ortho-photo-mosaics, for quantifying the badlands surface topographic changes, before and after at least one severe weather phenomenon (e.g., Medicane Ianos, Sept 2020).